A pharmacoepidemiological study of the association of suicide reattempt risk with psychotropic drug exposure. (June 2021) - Demesmaeker, Alice; Chazard, Emmanuel; Vaiva, Guillaume; Amad, Ali
Abstract: Introduction: Recent pharmacoepidemiological studies have suggested that consumption of certain classes of psychotropic drugs could be considered protective or risk factors for suicidal behaviour. The aim of the study was to evaluate the association between the risk of suicide reattempt within 6 and 14 months after a suicide attempt (SA) with the use of different classes of psychotropic drugs, combination pairs and treatment adequacy from inclusion through 6 and 14 months post-SA. Method: A prospective observational cohort of 972 subjects from the ALGOS study from January 2010 to February 2013 was used to evaluate the association of risk of suicide reattempt within 6 and 14 months with the use of different classes of psychotropic drugs (antidepressants, anxiolytics, antipsychotics, lithium, anticonvulsants, analgesics, opioid maintenance therapy and maintenance treatment for alcohol dependence). A multivariable Cox model was performed after imputation of missing data using the multiple imputation method. Results: Our main results did not show an association between psychotropic drug use and suicide reattempt after 6 months of follow-up. We demonstrated that the use of benzodiazepines (HR = 1.87 [1.25; 2.81], p < 0.01) and hypnotics (HR = 1.49 [1.03; 2.17], p = 0.04) or a combination of both (HR = 1.80 [1.17; 2.72], p = 0.01) were associated with suicide reattempt within 14 months after a previous SA. Conclusion: The early identification of a positive association between psychotropic drugs and the risk of suicidal behaviour is extremely important for prevention of suicide reattempts. Special precautions should be considered when prescribing psychotropic drugs for these subjects, particularly those at risk of suicide reattempt.